1987
DOI: 10.1002/eji.1830170415
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐linking of the T cell receptor complex with the subset‐specific differentiation antigen stimulates interleukin 2 receptor expression in human CD4 and CD8 T cells

Abstract: Nonpolymorphic interactions between the T cell differentiation antigens CD4 or CD8 and major histocompatibility complex (MHC)-encoded molecules have been postulated to participate in antigen recognition of MHC-restricted T cells. This would imply simultaneous binding of CD4/8 and of the T cell receptor complex (Ti/CD3) to MHC molecules on the stimulator or target cell. In this report experimental evidence is provided that simultaneous binding by antibodies of Ti/CD3 and of CD4 or CD8 leads to the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
1

Year Published

1987
1987
2002
2002

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(32 citation statements)
references
References 35 publications
4
27
1
Order By: Relevance
“…Therefore, Dynabeads-separated CD4+ T cells may be activated through both CD3 and CD4 molecules. Our results are supported by the results of Emmrich et al (1987) who reported that double immobilisation of anti-CD3 and anti-CD4 induced higher proliferation of CD4+ T cells compared with single immobilisation of anti-CD3 mAb. Thus, the separation procedure of CD4+ T cells using Dynabeads has two advantages over a method using a cell sorter; (1) The procedure is simple and rapid; (2) Dynabeads preparation causes augmented proliferation of CD4+ T cells against immobilised anti-CD3 plus IL-2.…”
Section: Cytotoxicity Assaysupporting
confidence: 91%
“…Therefore, Dynabeads-separated CD4+ T cells may be activated through both CD3 and CD4 molecules. Our results are supported by the results of Emmrich et al (1987) who reported that double immobilisation of anti-CD3 and anti-CD4 induced higher proliferation of CD4+ T cells compared with single immobilisation of anti-CD3 mAb. Thus, the separation procedure of CD4+ T cells using Dynabeads has two advantages over a method using a cell sorter; (1) The procedure is simple and rapid; (2) Dynabeads preparation causes augmented proliferation of CD4+ T cells against immobilised anti-CD3 plus IL-2.…”
Section: Cytotoxicity Assaysupporting
confidence: 91%
“…On the other hand, several recent reports highlight the importance of a physical association between CD4 and CD3-Ti complex during T-cell activation. First, cross-linking of CD3-Ti complex with CD4 molecule leads to synergistic activation, resulting in induction of IL-2 responsiveness and lymphoproliferation (33,34). Second, transfection of the CD4 gene enhances the reactivity of T-cell hybridomas if the stimulator cells express class II MHC molecule (35).…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear whether this effect is due to a negative regulatory signal transmitted directly to T cells, or whether there is steric hindrance of TCR crosslinking by the presence of anti-CD4 or anti-CD8 antibodies (Owens and Fazekas de St Groth, 1987). In contrast, when anti-CD4 or anti-CD8 monoclonal antibodies are cross-linked to anti-TCR antibodies, a marked synergy in activation is observed (Emmrich et al, 1987;Walker et al, 1987). It has also been speculated that CD4 or CD8 may become physically associated with the TCR (Saizawa et al, 1987;Takada and Engleman, 1987;Rivas et al, 1988).…”
Section: Introductionmentioning
confidence: 99%